Strategi Penguatan Ekonomi Masyarakat Lokal Melalui Pariwisata Syariah Pada Kawasan Destinasi Wisata Ngarai Sianok Kota Bukittinggi - Nori; Zulhelmi (STKIP Subang, 2026)
This study aims to formulate development strategies for Islamic tourism to strengthen the local economy in the Ngarai Sianok tourism area, Bukittinggi City. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. Informants consisted of local communities, tourism business actors, tourism awareness groups (Pokdarwis), and representatives of local government. The data were analyzed using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to map the internal and external conditions of the destination and formulate appropriate development strategies. The findings indicate that the application of Islamic tourism has great potential to enhance local community welfare, particularly through active participation in maintaining Islamic values and managing tourism activities. The SWOT analysis revealed that the S–O (Strengths–Opportunities) strategy is the most potential, with the highest score of 3.60. Recommended strategies include optimizing the natural beauty and Islamic culture of Minangkabau, strengthening community capacity in halal tourism services, expanding digital promotion with Islamic narratives, and improving tourism facilities that comply with Islamic principles. With the right and collaborative strategy, the development of Islamic tourism in Ngarai Sianok is expected to not only reinforce the region’s religious identity but also contribute to sustainable economic growth for the local community.